The Impact of Church Leadership on Children’s Ministry Growth: A Case Study of St. Philip’s Parish, Diocese of Northern Uganda - Daniel Omony (Uganda Christian University, 2024)
One of the most important resources in the kingdom of God is children. The best time to promote spiritual growth and evangelism is during childhood. The spread of the gospel and the development of children's spirituality are closely linked to the growth of the church both in terms of number and quality. Thus, church at St. Philip has seen development because of prioritizing their children's ministries. Put another way, the church's future cannot succeed if the children's ministry fails. The children's ministry of St. Philips Parish Church strives to achieve the ministry's growth. This study aims to identify the variables influencing children ministry growth at St. Philip Parish at the DNU. The study aimed to investigate the following specific topics: the impact of church leadership on the development and growth of children ministry at St. Philip Parish in the Diocese of Northern Uganda; the relationship between resource allocation practices and the ministry's growth trajectory; and the analysis of the impact of personnel dynamics, such as recruitment, training and engagement on the ministry's sustainability and growth at St. Philip Parish in the Diocese of Northern Uganda (DNU). This was carried out in order to support the growth of the children ministry at St. Philip Parish in the Diocese of Northern Uganda. A census of thirty people, including Sunday school teachers, priest/church leaders and elders from St. Philip parish has been engaged by the team. The target demographic of St. Philip parish, which includes the randomly chosen priest/church leaders, Sunday school teachers and elders, were asked uestions in order to gather primary data from respondents to do the statistical analysis necessary to meet the study's objectives, SPSS was used. After that, every statistical test was run at a confidence level.